2017
DOI: 10.2319/102916-779.1
|View full text |Cite
|
Sign up to set email alerts
|

Twin Block appliance with acrylic capping does not have a significant inhibitory effect on lower incisor proclination

Abstract: Objective: To investigate the effect of acrylic capping, treatment duration, overjet, and lower incisor inclination on the posttreatment tooth position in patients treated with 2 Twin Block (TB) appliance versions. Materials and Methods: Cephalograms of 56 patients with Class II malocclusion (21 boys, 35 girls; mean age before treatment [T1] ¼ 12.5 years; standard deviation, 0.7) treated with a TB appliance with either acrylic capping or ball-ended clasps on lower incisors were retrospectively collected and tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 26 publications
1
11
1
1
Order By: Relevance
“…Interestingly, CephNinja, unlike OneCeph, 20,21 c Values with unacceptable reliability (ie, ,.7). 19 does not have incorporated features to assist the user with relocating points on the mobile touchscreen in case of wrong identification. Evaluation of cephalometric measurements deriving from two apps installed on an iPad (ie, CephNinja and SmartCeph) compared with Pro Dolphin Imaging computer software showed statistically significant differences in 56.3-62.5% of the measurements.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, CephNinja, unlike OneCeph, 20,21 c Values with unacceptable reliability (ie, ,.7). 19 does not have incorporated features to assist the user with relocating points on the mobile touchscreen in case of wrong identification. Evaluation of cephalometric measurements deriving from two apps installed on an iPad (ie, CephNinja and SmartCeph) compared with Pro Dolphin Imaging computer software showed statistically significant differences in 56.3-62.5% of the measurements.…”
Section: Discussionmentioning
confidence: 99%
“…The free versions of the CephNinja and OneCeph 15 apps were downloaded from the Google Play Store on March 30, 2018 (Google Inc, Mountain View, Calif) on a Samsung Galaxy S8 smartphone (Samsung Telecommunications, Suwon, South Korea). Viewbox, a CE-certified computerized cephalometric analysis program broadly used in orthodontic research, [16][17][18][19] was installed on a laptop (Microsoft Surface Laptop Core, i8, 8-256 GB, Microsoft Corporation, Redmond, Wash) and served as the gold standard. To eliminate interobserver variability and to focus on the intertool variability, a single examiner (Dr Livas) traced the radiographs randomly first using Viewbox, then One-Ceph, and finally CephNinja.…”
Section: Tracing Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4] In their study investigating the long-term effects of protrusive function, McNamara and Bryan 5 reported that mandibular length increased with remodeling of the posterior and postero-superior surfaces of the condyle. Contrary to these studies, other authors [6][7][8] reported that functional orthopedic treatment induced little change in the bony elements of the craniofacial system and argued that the effect was limited to the dentoalveolar region. Discrepancies between the findings reported in these studies may be attributable to the variety of measurement methods used, as well as to the fact that most measurements were based on cephalometric radiographs and could not reflect changes in the osseous structure of the mandibular region.…”
Section: Introductionmentioning
confidence: 87%
“…11 Various design and modification of twin-block appliances have been used to decrease this side effect. 2,5,12 Treatment effects of removable orthodontic appliances, irrespective of the particular individual therapeutic intervention and mode of action largely depend on the patient cooperation. 13 One of the most important factors on patients' cooperation is the appearance of the appliance that may be unpleasant in social interactions.…”
Section: Introductionmentioning
confidence: 99%